Writing settlement after Idle No More: non-indigenous responses in Anglo-Canadian poetry - Roberts, Gillian (University of Toronto Press, 2017)
This article examines the representation of settlement in Canada in the wake of Idle No More in recent Anglo-Canadian literature. It argues that Idle No More engendered a new vocabulary for settler-invader citizens to position themselves in relation to this Indigenous movement, with non-Indigenous Canadians self-identifying as “settlers” and “allies” as a means of both orienting themselves with respect to Indigenous resistance to the settler-invader nation-state and signalling an attempted solidarity with Idle No More that would not lapse into appropriation. Four very different poetic texts by non-Indigenous authors demonstrate this reconsideration of settlement in the wake of Idle No More: Arleen Paré’s Lake of Two Mountains (2014); Rachel Zolf’s Janey’s Arcadia (2014); Rita Wong’s undercurrent (2015); and Shane Rhodes’s X (2013). Although only the latter two of these collections make explicit reference to Idle No More, all four of these texts engage with historical and current colonialisms, relationships to land and water, and relationships between Indigenous peoples and settler-invaders, providing examples of new understandings and representations of (neo)colonial settlement in post-Idle No More Canada.